Effectiveness of Combination of Thunder Fire Moxibustion with Other Forms of Traditional Chinese Medicine for Osteoarthritis Knee: A Meta-Analysis - Wei W; Qin Y; Lin J (Journal of Pain Research, 2025)
Wei Wei,1,* Yeyu Qin,2,* Jie Lin1 1Haikou Affiliated Hospital of Central South University Xiangya School of Medicine, Haikou, Hainan, 572023, People’s Republic of China; 2Department of Pharmacy, Hainan General Hospital, Haikou, Hainan, 570311, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Lin, Haikou Affiliated Hospital of Central South University Xiangya School of Medicine, Haikou, Hainan, 572023, People’s Republic of China, Email linjie9261@sina.comBackground: Given the prevalence of osteoarthritis and the growing interest in alternative treatments, there is a need to provide a comprehensive evaluation of this integrated TCM approach. Reviews are required to understand the potential benefits and safety of the combination therapy compared to conventional treatments. Hence, this meta-analysis investigates the effectiveness of combining Thunder Fire Moxibustion with other Traditional Chinese Medicine (TCM) modalities, specifically acupuncture and herbal formulas, in treating knee osteoarthritis.Methods: A comprehensive literature search across databases like PubMed Central, EMBASE, MEDLINE, and others was conducted. The inclusion criteria focused on randomized controlled trials involving patients with knee osteoarthritis, comparing the effectiveness of Thunder Fire Moxibustion combined with other TCM modalities against standard care. The Cochrane Risk of Bias tool was used for bias assessment, and a random-effects inverse-variance model for meta-analysis.Results: Out of 1467 records, 7 studies met the inclusion criteria. The pooled Risk Ratio (RR) for total effective rate was 1.119, indicating a significant effect of the combined TCM treatment. Subgroup analysis showed a pooled RR of 1.130 for acupuncture combinations and 1.103 for herbal TCM combinations. The incidence of adverse reactions had a non-significant pooled RR of 0.572. The GRADE assessment indicated a low overall quality of evidence due to risks of bias and publication bias.Conclusion: The combination of Thunder Fire Moxibustion with other TCM modalities shows potential effectiveness in treating knee osteoarthritis, with minimal adverse reactions. However, the low quality of evidence suggests a need for more rigorous studies to confirm these findings.Keywords: acupuncture, meta-analysis, moxibustion, osteoarthritis